Clustered auction strategies and performance outcomes in the Indian Premier League - Joglekar, D. J.; Pifer, N. D.; Narayanan, S. (Journal of Sports Analytics, 2025)
This study identified roster-formulation strategies in the Indian Premier League (IPL) auction and explored relationships to team performance. Using data from 127 team-seasons across 16 IPL seasons, teams were clustered into strategic groups based on 27 standardized features, including spending patterns, player attributes, and retention behaviors. Three distinct groups emerged from the cluster analysis. These clusters primarily differed in spending behavior, salary distribution, and player characteristics. Regression analyses indicated minimal short-term relationships between a team's cluster assignment and its subsequent winning percentage or playoff qualification, although a few multi-year sequences displayed significant effects in relation to a baseline strategy. The observedly weak links between labor market strategy and team performance are likely due to the league's auction-based labor market and structural regulations that promote competitive parity. These results provided insights into strategic planning under salary constraints and potential links to team performance.